Plan de negocio para la creación de un salón de uñas especializado en servicios de manicure y pedicure - Pazmiño Miranda, Karen Hellen (2024)
The business plan focuses on the creation of a competitive and sustainable microenterprise that will satisfy a large existing demand. With the aim of developing a nail salon specialized in manicure and pedicure services in the Batallón del Suburbio that offers quality services. The study approach is mixed using quantitative and qualitative tools to collect relevant information. Qualitatively, it will include interviews with nail salon owners in order to see the key points. On the other hand, the quantitative, statistical information will be presented on the size of the sample, the current demand in the market, this will be through a survey data will be collected to know the preferences of the target audience interested in the nail salon. The business plan will include an analysis to understand your strengths and opportunities in the market. The business will focus on providing a unique value proposition in the nail salon it will offer to its clients, as well as marketing strategies to attract and retain potential future clients. The study will evaluate the feasibility of the project and determine the necessary investments, operating costs, business profitability and market demand.